HIV/AIDS in Latin American countries : the challenges ahead - Abreu, Anabela Garcia; Noguer, Isabel; Cowgill, Karen (Washington, DC : World Bank, 2003)
HIV/AIDS in Latin American countries presents new and updated information about the extent and trends of the HIV/AIDS epidemic in Latin America. it evaluated current national surveillance capacity, assesses the national responses of the health sector to the epidemic on a country by country basis, identifies key areas in which specific interventions are urgently needed and outlines the challenges ahead.
Includes index.
Includes bibliographical references (p. [275]-295).
nmn, 08/08/2016
Loans
Keywords: AIDS (Disease).